How to design collaboration strategies in high-output and low-output networks: considering the role of internal social capital. Issue 1 (2nd January 2023) - Pan, Wenhui; Zhao, Pengwei; Ding, Xianfeng
ABSTRACT: The design of comprehensive collaboration strategies is important to improve academic output efficiently, and previous studies have focused on collaboration strategies considering internal social capital. However, internal social capital in teams with different academic output is not always the same. In this study, we expand the research team into a collaboration network, and try to analyse in high-output and low-put collaboration networks, how internal social capital affects the collaboration strategy's impact on the academic output. Using the data collected from the NSFC, the results indicate that internal social capital enhances the impact of collaboration strategy on academic output in high-output collaboration networks, while internal social capital hinders this relationship in low-output collaboration networks. The findings provide some practical implications for leaders in designing collaboration strategies, and for government agencies in designing funding plans.